Comparative performance of IP-10-Based assays for immune detection of Mycobacterium tuberculosis infection: a cross-sectional evaluation - Alexandru Stoichita; Madalina Burecu; Camelia Nita; Cristina Teleaga; Alexandru Daniel Radu; Mihaela Mihai; Beatrice Mahler; Elmira Ibraim (Frontiers in Medicine, 2026)
Background Reliable immune-based detection of Mycobacterium tuberculosis infection remains challenging, particularly in TB contacts and individuals with immune dysregulation. IP-10 is produced at substantially higher concentrations than IFN-γ and represents a promising biomarker for enhancing IGRA-based immune detection. This study evaluated the comparative performance of two IP-10-based assays, RIDA ® QUICK TB and RIDA ® SCREEN TB, in relation to QuantiFERON-TB Gold Plus. Methods This cross-sectional comparative evaluation enrolled 99 adults: 49 with culture-confirmed active pulmonary TB, 30 close TB contacts, and 20 individuals with autoimmune disease. All participants underwent RIDA ® QUICK TB, RIDA ® SCREEN TB, and QFT-Plus testing. Because no independent gold standard exists for latent tuberculosis infection, assay performance was assessed using positivity rates, overall percent agreement, positive percent agreement, negative percent agreement, Cohen’s kappa, McNemar testing, and discordance analysis. In the culture-confirmed active TB subgroup, the proportion of positive immune-test results was reported descriptively. Results Among culture-confirmed active TB cases, RIDA ® QUICK TB was positive in 42/49 participants, while RIDA ® SCREEN TB was positive in 45/49 participants, compared with 35/49 for QFT-Plus. This estimate reflects immune-test positivity among culture-confirmed active TB cases and should not be interpreted as sensitivity for latent tuberculosis infection. Across the full cohort, both IP-10-based assays yielded higher positivity rates than QFT-Plus, particularly in the active TB subgroup. Agreement with QFT-Plus varied by clinical subgroup and was strongest among TB contacts, supporting the immunological concordance of the evaluated platforms in this population. ROC analyses using QFT-Plus as the comparator demonstrated good immunological concordance between the IP-10-based assays and QFT-Plus-defined immune status. These analyses evaluate agreement between immune-response platforms and do not represent diagnostic accuracy against a definitive microbiological standard. Conclusion RIDA ® QUICK TB and RIDA ® SCREEN TB demonstrated encouraging performance, with high positivity among culture-confirmed active TB cases and clinically relevant agreement with QFT-Plus across distinct participant groups. These findings support the potential role of IP-10-based assays as complementary immune-based tools for TB infection evaluation, particularly in settings where enhanced immune-response detection may be useful. Larger, clinically characterized and longitudinal studies are warranted to further define specificity, predictive value, and integration into LTBI screening strategies.